2020
DOI: 10.4269/ajtmh.20-0035
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Management of Pit Viper Envenoming without Antivenom: A Case Series

Abstract: Pit viper envenoming is common in the hilly and the Himalayan regions of Nepal. Antivenom present in Nepal is unlikely to neutralize the venom of these pit vipers, although it has been used often by the healthcare providers in the clinical practice. Here, we report 15 cases of snakebite with a deranged coagulation profile. All patients recovered from envenoming on conservative management and without the administration of antivenom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Of the 132 studies included for full-text review, 11 met the inclusion criteria. Authors from a further 29 studies that reported methodology suggesting synchronous 20WBCT and clotting sample collection were contacted, and a further four studies (from three papers) were included [5,30,31]. Thus, 15 studies were included in the systematic review (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 132 studies included for full-text review, 11 met the inclusion criteria. Authors from a further 29 studies that reported methodology suggesting synchronous 20WBCT and clotting sample collection were contacted, and a further four studies (from three papers) were included [5,30,31]. Thus, 15 studies were included in the systematic review (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Individual patient data (n = 1,865, 82.2%), were either reported, displayed in figures or provided upon request in nine studies [5,16,[30][31][32]34,36,37]. In these studies, the median INR for patients with a false negative 20WBCT (n = 33) was 1.9 (IQR 1.6 to 12.0, skewness of 1.06 and kurtosis of -0.83).…”
Section: A Comparison Of True Positive and False Negative 20wbctmentioning
confidence: 99%
See 2 more Smart Citations
“…Navin Bhatt et al ,[ 9 ] (2020) published a case series on American Journal of Tropical Medicine and Hygiene, involving 15 cases of viper bite who were treated conservatively without ASV. All the 15 cases had coagulopathy with deranged coagulation parameters (prolonged WBCT), and all of them were discharged within 3-8 days of snake bite after resolution of coagulopathy.…”
Section: Discussionmentioning
confidence: 99%